People, Actors, and the Humanizing of Institutional Theory. (28th February 2020) - Voronov, Maxim; Weber, Klaus
Abstract: In much contemporary institutional scholarship, the term 'actor' is used as a shorthand for any entity imbued with agency. Talking about actors in institutions thus serves the necessity of allocating agency before returning to the analysis of institutional structures and processes. We find this approach to actorhood limiting, conceptually and normatively. Grounded in the perspective of pragmatist phenomenology, we assert the need for distinguishing between persons and actors, and the value of integrating the person into institutional analysis. We conceive of persons as humans with a reflective capacity and sense of self, who engage with multiple institutions through the performance of institutional roles. People may acquire actorhood by temporarily aligning their self with what is expected from a particular actor‐role in an institutional order. Conversely, institutions enter people's lifeworld as they are personified in people's social performances. We outline this perspective and examine conceptual and normative implications that arise from the integration of human experience in institutional analysis.